2001
DOI: 10.2466/pms.2001.92.3.933
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Coaches' Perceptions of the Causes of Home Advantage

Abstract: This study investigated the personal experiences of 144 high school coaches in terms of their perceptions of the causes of the home advantage. Surveys were distributed to varsity coaches of local high school sports asking them to assign a percentage value to each of the most common explanations of -the home advantage, reflecting the perceived importance of each, e.g., social support, travel or fatigue, site familiarity, officials' bias, and self-fulfilling prophecy. A 3 x 6 repeated-measures analysis of varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The custom-designed survey was developed using key areas that have previously been investigated, such as perceptions of the venue, crowd, fans, travel, referees ( Fothergill, et al ., 2014 ), and the self-fulfi lling prophecy ( Gayton, et al ., 2001 ). The purpose of the study was to pilot the survey with a team identifi ed as having a HA and who did not share their home ground with another team.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The custom-designed survey was developed using key areas that have previously been investigated, such as perceptions of the venue, crowd, fans, travel, referees ( Fothergill, et al ., 2014 ), and the self-fulfi lling prophecy ( Gayton, et al ., 2001 ). The purpose of the study was to pilot the survey with a team identifi ed as having a HA and who did not share their home ground with another team.…”
Section: Methodsmentioning
confidence: 99%
“…The participants indicated that they felt supported by the crowd when playing at home, and their performance increased compared to playing away from home where they suggested the visiting team often had limited access to facilities, including smaller, inferior dressing rooms. Similarly, high school coaches suggested site familiarity was the most likely factor contributing to home advantage ( Gayton, Broida, & Elgee, 2001 ). Additionally, Bray and Widmeyer (2000 ) reported that female athletes on a basketball team with an identifi ed home advantage suggested that they had a greater chance of winning at home due to familiarity with the home court, support from the home crowd, and reduced travel prior to the game ( Bray & Widmeyer, 2000 ).…”
mentioning
confidence: 99%
“…The home advantage in sport arises from a psychological state in which athletes and fans develop territoriality over their home arena, resulting in a strong desire to defend their home territory (Neave and Wolfson, 2003). When games are played on home turf, athletes have reported higher site familiarity (Gayton et al, 2001), lower travel fatigue (Brown et al, 2002), greater self-efficacy and confidence (Bray et al, 2002) as underlying factors influencing performance. Furthermore, sport fans have also reported being more reactive to their team's performance when a game is played on home turf (Strauss, 2002), resulting in greater positive team association after wins and greater negative team dissociation after losses (Bernache-Assollant et al, 2016;Dalakas et al, 2004;Jensen et al, 2016;Mudrick et al, 2016).…”
Section: Excitation-transfer Theorymentioning
confidence: 99%
“…In addition, the rugby players suggested sleeping arrangements and familiarity with the weather as crucial variables. However, among these various factors, field familiarity was found to be perceived as the most important factor for athletes as well as coaches ( Bray et al, 1998 ; Gayton et al, 2001 ; Fothergill et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%